Optimizing Base Salary, Performance Incentives, and Welfare Benefits to Improve Lecturer Well-being and Educational Quality in Private Islamic Religious Higher Education Institutions - Juhainah, Juhainah; Pahrudin, Agus; Fakhri, Jamal; Yuberti, Yuberti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Private Islamic Religious Higher Education Institutions in Indonesia, particularly in Lampung Province, continue to face significant challenges in enhancing lecturer welfare due to suboptimal compensation policies. Disparities between workload and financial incentives often diminish lecturers’ motivation and negatively impact the quality of education. This study aims to examine the implementation of compensation policies in Private Islamic Religious Higher Education Institutions, evaluate their effects on lecturer welfare and academic performance, and propose realistic optimization strategies. Framed by Herzberg’s Two-Factor Theory, this qualitative study used a case study approach involving in-depth interviews, observations, and document analysis across three Private Islamic Religious Higher Education Institutions  with varying institutional characteristics. The findings show that compensation components—including base salary, performance bonuses, welfare benefits, and professional development support are inconsistently implemented and often constrained by limited budgets, lack of transparency, and institutional policy gaps. These deficiencies contribute to low job satisfaction and hinder efforts to improve teaching and research. The study recommends the adoption of a transparent, performance-based compensation framework supported by improved financial governance and alternative funding strategies such as corporate social responsibility (CSR) partnerships, waqf-based endowments, and performance-based grants. Strengthened collaboration between institutions, government, and external stakeholders is also essential to ensure sustainable improvement in lecturer welfare and education quality in Private Islamic Religious Higher Education Institutions.